2020
DOI: 10.1101/2020.04.23.20076943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in COVID-19 Outbreaks at U.S. State and County Levels

Abstract: Background. The COVID-19 pandemic poses an unprecedented threat to the health and economic prosperity of the world's population. Yet, some countries or regions within a country appear to be affected in different ways.Objectives. This research aims to understand whether the outbreak varies significantly between U.S. states and counties. Methods.A statistical model is estimated using publicly available outbreak data in the U.S., and regional differences are statistically analyzed.Results. There is significant va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…1 The local press and epidemiological research alike have reported local differences in the outbreak. 2 A community's susceptibility to any virus is determined by a variety of factors, inter alia, biological determinants, demographic profiles, and socioeconomic characteristics. 3 These factors vary significantly across the U.S.; for instance, COVID-19 fatalities in New York, an epicenter of the outbreak in the U.S., disproportionally affect males and people belonging to older age groups, from Black/African and Hispanic ethnicities, and with certain comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…1 The local press and epidemiological research alike have reported local differences in the outbreak. 2 A community's susceptibility to any virus is determined by a variety of factors, inter alia, biological determinants, demographic profiles, and socioeconomic characteristics. 3 These factors vary significantly across the U.S.; for instance, COVID-19 fatalities in New York, an epicenter of the outbreak in the U.S., disproportionally affect males and people belonging to older age groups, from Black/African and Hispanic ethnicities, and with certain comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The local press and epidemiological research alike have reported local differences in the outbreak. 2 A community's susceptibility to any virus is determined by a variety of factors, inter alia, biological determinants, demographic profiles, and socioeconomic characteristics. 3 These factors vary significantly across the U.S.; for instance, COVID-19 fatalities in New York, an epicenter of the outbreak in the U.S., disproportionally affect males and people belonging to older age groups, from Black/African and Hispanic ethnicities, and with certain comorbidities.…”
mentioning
confidence: 99%
“…First, we note that contextual factors influence the COVID-19 outbreak. Because significant variations in the outbreak exist between states and counties within a state (see Figures 1 and 2), 2 we recommend policy makers to look at pandemics from the smallest subdivision possible for effective implementation of countermeasures and provision of critical resources. Second, we develop an understanding of how regional cultural differences relate to outbreak variations, driven by specific psychological functioning of individuals and the enduring effects of such differences on political processes, governmental institutions, and public policies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have tracked regional differences in COVID-19 outcomes (e.g., cases, deaths), 5 fewer have examined regional differences in physical distancing behaviors over time. This is a notable omission because physical distancing trends are predictive of later COVID-19 outcomes, 6 and access to physical distancing may be structurally constrained by U.S. region.…”
mentioning
confidence: 99%